2018
DOI: 10.3390/buildings8020015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Self-Compacting Mortar Incorporating Recycled Glass Aggregate

Abstract: Abstract:This experimental research is focused on the development of self-compacting mortar incorporating recycled glass aggregate (SCM-RGA) as partial substitution of fine aggregate (wt 0%, 10%, 20%, 30%, 40% and 50%). The fresh and hardened mechanical properties as well as durability of SCM-RGA mixes were investigated. Limestone powder (LP) was used as filler that constitutes 20% of the powder volume to reduce the amount of cement. The SCM-RGA mixtures were designed based on Japanese mix design method. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 41 publications
4
16
1
2
Order By: Relevance
“…The test results of the rapid mortar bar expansion indicate that the replacement of 20% of Portland cement with ground glass powder (specific surface area—467 m 2 /kg) more than halves the expansion due to the alkali–silica reaction (ASR) [22]. Tuaum et al observed that as the content of glass aggregate increased, ASR expansion also increased [23]. Similar processes can take place using a fine expanded glass LWA.…”
Section: Introductionmentioning
confidence: 99%
“…The test results of the rapid mortar bar expansion indicate that the replacement of 20% of Portland cement with ground glass powder (specific surface area—467 m 2 /kg) more than halves the expansion due to the alkali–silica reaction (ASR) [22]. Tuaum et al observed that as the content of glass aggregate increased, ASR expansion also increased [23]. Similar processes can take place using a fine expanded glass LWA.…”
Section: Introductionmentioning
confidence: 99%
“…Where VP is the volume of the paste previously determined. The mixing process was carried out as proposed [34]. The materials used and the mixing process are shown in Table 1.…”
Section: Dosing and Mixing Methodsmentioning
confidence: 99%
“…Firstly, glass improves workability by reducing water adsorption and friction due to its dense microstructure and smooth surface. Indeed, WG has been used to create SCC that is vibration-free during construction [81][82][83][84][85]. Secondly, glass can reduce workability due to extremely fine glass particles; the surface-to-volume ratio increases, increasing water adsorption.…”
Section: Waste Glass Utilization In Cement-based Materialsmentioning
confidence: 99%